2019
DOI: 10.1002/dac.3919
|View full text |Cite
|
Sign up to set email alerts
|

Secure communication in cognitive radio networks with untrusted AF relays

Abstract: Summary In this paper, two underlay based cognitive cooperative radio networks, each with one secondary source (SS), one secondary destination (SD), N untrusted secondary amplify and forward relays (USAFRs), one primary transmitter, and one primary receiver (PU‐RX), are considered for evaluating the secrecy performance. The SS sends the information to the SD in two time slots via multiple USAFRs in the absence of direct link between SS and SD. In the first time slot, SS and SD transmit the message and jamming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Harvesting energy at SU l can be written as 24 El=ηρl{}PT1false|hlfalse|2false(Dp1lfalse)ν+PT2false|glfalse|2false(Dp2lfalse)ν+j=1NPIjlfalse|ϱjlfalse|2false(djlfalse)ντT where ρl (0 <ρl< 1) indicates PS factor. ρl fraction of received power is used for EH and rest ( 1ρl) portion of received power is applied for information decoding purpose during the time interval τT.…”
Section: Description Of System Architecture and Signal Modellingmentioning
confidence: 99%
“…Harvesting energy at SU l can be written as 24 El=ηρl{}PT1false|hlfalse|2false(Dp1lfalse)ν+PT2false|glfalse|2false(Dp2lfalse)ν+j=1NPIjlfalse|ϱjlfalse|2false(djlfalse)ντT where ρl (0 <ρl< 1) indicates PS factor. ρl fraction of received power is used for EH and rest ( 1ρl) portion of received power is applied for information decoding purpose during the time interval τT.…”
Section: Description Of System Architecture and Signal Modellingmentioning
confidence: 99%
“…In addition, the combination of these two protocols has also been applied in the literature to increase the amount of harvested energy and the performance of SWIPT systems. Various works such as [28][29][30] demonstrated that PS protocol can provide better secrecy outage probability (SOP) and ergodic secrecy rate than TS protocol. However, the throughput of TS protocol outperforms that of PS protocol at relatively low signal-to-noise-ratio (SNR) and high trans-mission rate [31].…”
Section: System Modelsmentioning
confidence: 99%